Pixel art for game developers - Silber, Daniel (Boca Raton : CRC Press, 2016)
"Uncover the secrets to creating stunning graphics with Pixel Art for Game Developers. ... The book provides an introduction to Pixel Art, its utility, foundational elements, and concepts such as light and shadow. It offers tutorials on creating animations and serves as a functional guide for the most common methodology in 2D game development."--Back cover.
-- Why pixel art? -- Pixel art : the technology of yesterday...today! -- Who am I and why do I know so much about pixel art? -- Software : set up your working environment -- Making pixel art : doing lines -- Coloring inside the lines -- Drawing secrets revealed : it's all smoke and mirrors -- Animating pixels : the shock and horror of being flashed by a pixel -- Tiled backgrounds -- You're doing it wrong : things to avoid -- Interviews with game developers -- Resources -- Afterword : Some thoughts on why I wrote this book.
"An AK Peters Book"--Cover.
"Version date: 20150618"--Title page verso.
Includes bibliographical references (pages 227-228) and index.
Keywords: Computer graphics; Computer games -- Design